The Impact of Supervisor Support on Employee-Related Outcomes Through Work Engagement - Pires, Maria Leonor Abrantes (2021)
One of the main concerns for organizations management is employee related outcomes, given their impact on organizational performance. Relatively less attention is given to organizational features that may intervene in the process, such as organizational culture or climate, and direct supervision. We study the impact of supervisor support perceptions on absenteeism and on burnout, trough the mediation of work engagement, while controlling the effect of perceived organizational values. Hypotheses were tested on a 43850 multi-country sample, through multiple regression-based analyses. Results show that supervisor support precedes work engagement, a relationship moderated by organizational values; supervisor support, partially mediated by work engagement relates negatively with absenteeism and exhaustion, prevent cynicism and increases perceptions of self-efficacy. The findings allow us to discuss the role of supervisor support on work engagement and their effects on employee outcomes.